ANALISIS INTEGRATED MARKETING COMMUNICATION (IMC) PADA PRODUK TABUNGANKU BTN KCP SYARIAH BUKITTINGGI - Nailatul Fadhilah; Rusydi Fauzan (CV. Adiba Aisha Amira, 2024)
This research aims to analyze Integrated Marketing Communication (IMC) and Integrated Marketing Communication (IMC) indicators in the TabunganKu BTN KCP Syariah Bukittinggi product. The type of research used by the author is descriptive qualitative because it produces data in the form of spoken and written words from the people interviewed and uses primary and secondary data. Data collection techniques by means of observation, interviews and documentation. Next, data analysis uses data collection methods, data triangulation, and drawing conclusions. The results of the research that has been carried out can be concluded that the Integrated Marketing Communication Analysis of TabunganKu BTN KCP Syariah Bukittinggi Products consists of Advertising, Sales Promotion, Public Relations, Personal Selling, Direct Marketing ( Direct Marketing), Events and Experience. Of these six variables, there are 4 variables that have been carried out well, namely sales promotion, public relations, personal selling and direct marketing, while two other variables are said to be not good, namely advertising ( Advertising) and events and experiences (Events and Experience).